Athlete ECG T-wave abnormality interpretation patterns by non-experts - Asad J. Torabi; Omar D. Nahhas; Reginald E. Dunn; Matthew W. Martinez; Andrew M. Tucker; Andrew E. Lincoln; Richard J. Kovacs; Michael S. Emery (American Heart Journal Plus, 2022)
Background: The presence of T-wave abnormalities (TWA) on an athlete's electrocardiogram (ECG) presents as a diagnostic challenge for physicians. Types of TWA patterns classified as abnormal by inexperienced readers have not been systematically analyzed. Methods: ECGs from the 2011–2015 National Football League Scouting Combine (initially interpreted by general cardiologists) were retrospectively reviewed by expert sports cardiologists with strict application of the 2017 International Criteria. Patterns of TWA that were altered from the original interpretation were analyzed. Results: The study included 1643 athletes (mean age 22 years). There was a 67 % reduction in the number of athletes with any TWA (p < 0.001) with 111 ECGs changed to normal. Inferior TWA was the most common interpreted initial ECG abnormality altered followed by anterior and lateral. Discussion: This analysis revealed an initial high rate of TWA by non-expert readers. Tailored education programs to physicians who interpret athlete ECGs should highlight these specific T-wave patterns. We see this as an opportunity to make more clinicians aware of ECG interpretation guidelines as sports trained cardiologists are mostly self-taught.